The changing policy environment facing African agriculture - Chigunta, Francis; Herbert, Ross; Johnson, Michael E.; Mkandawire, Richard (International Food Policy Research Institute, 2004)
According to the authors, "Both national and international economic environments have changed substantially in the past decade and a half. As they look to the future, African policymakers will have to apply the lessons of the past in a very different environment". The brief explains the changes in both the international and national environment: Global consolidation in food retailing; Shifting composition of traded goods; Growing regional demand for staples; Advances in science and technology; Heavy farm subsidies in industrialized countries; and Land pressure.